The Influence of Kaolinite and pH on Permeability in the Zubair Reservoir in the North Rumaila Oilfield, Southern Iraq - Awadh, Salih; Al-Yaseri, Abdullah; Hussein, Ali (Iraqi Journal of Science, 2023)
This research involves the study of permeability declination as a result of kaolinite due to the changing in pH in the Zubair reservoir (Lower Cretaceous) during the secondary production by water injection method. Four wells and six core samples within the North Rumaila field are studied, Minerals have been diagnosed by XRD and this specific site of clay minerals was diagnosed within the core samples by scanning electron microscopy (SEM). The core samples are also studied petrogrphically using the polarizing microscope and found that they mainly consist of quartz, while the predominant clay is kaolinite. The effect of pH on the values of permeability was examined through a series of laboratory experiments, as it has been tested in the cases of gradual sudden increase form acidic to alkaline. Petrophysical properties (porosity and initial permeability) were measured a prior to testing. After performing these tests, the final permeability was also measured as well as the rate of formation damage. The final permeability decreased gradually at a rate of 20-30% M Darcy during the injection out with solution of pH 3 to 11 with getting formation damage up to 25%. While in the case injection with sudden increase pH from acid to alkaline directly, there has been a rapid and substantial reduction in the final permeability as average of 28% -72%, with a formation damaged rate of 44%. The results confirmed that the reason of the decrease in the permeability is due to the kaolinite mineral which is subject to the dispersion phenomenon during the change in pH, and the acidic environment is suitable for the reservoir, and does not lead to a reduction in permeability.